NILAI PENDIDIKAN KARAKTER PERJUANGAN I GUSTI NGURAH RAI DALAM PERANG MEMPERTAHANKAN KEMERDEKAAN INDONESIA SERTA POTENSINYA SEBAGAI SUMBER PEMBENTUKAN KARAKTER BANGSA - I Nyoman Bayu Pramartha; Ni Putu Yuniarika Parwati (Widyadari, 2023)
This study tries to examine the value of character education in the struggle of I Gusti Ngurah Rai in the War of Independence to defend Indonesia's independence. This study also examines how the potential of I Gusti Ngurah Rai's struggle in defending Indonesia's independence is to be used as a source of national character formation. The research method uses qualitative methods with analytical descriptive explanations. The stages used in the research are starting from the stage of determining the topic, observation, interviews, documentation studies, and literature studies. The results show that the value of character education is very relevant to the story of the struggle of I Gusti Ngurah Rai in defending independence. The value of character education contained in the struggle of I Gusti Ngurah Rai in maintaining independence has great potential to be used as a source of national character formation. The conclusion of this study: the value of character education contained in the struggle of I Gusti Ngurah Rai, among others, such as, religious, honest, tolerance, discipline, democracy, love for the homeland, social care and responsibility. The value of character education in the story of I Gusti Ngurah Rai's struggle has great potential to be used as a source of national character formation. The formation of a nation's character with a high historical awareness will lead to a figure who is intelligent and has a high spirit of patriotism.